PROYEKSI KEBUTUHAN AIR DOMESTIK DAN PARIWISATA UNTUK PENGEMBANGAN WILAYAH DI LABUAN BAJO - Farah Syuraih Muchtar; Hayati Sari Hasibuan; Philiphi de Rozari (Universitas Lambung Mangkurat, 2023)
Clean water is essential for the welfare of life and regional development. As one of the super-priority tourism destinations, Labuan Bajo continues to experience growth and infrastructure development to support tourism development. Regional development in Labuan Bajo, classified as a semi-arid area for tourism needs, can potentially cause a clean water crisis. Tourism often uses clean water, triggering social conflicts with local communities. This study aims to analyze and project domestic clean water needs and tourism water needs in Labuan Bajo. The method used in this research is a quantitative method with data collection instruments by literature studies, field observations, and distributing questionnaires to 261 respondents in the urban area of Labuan Bajo. The results showed that the domestic water demand in Labuan Bajo was 90,23 liters/day/person or greater than the reference standard for the Directorate General of Human Settlement and Water Resources regarding the average domestic water demand in small town areas. The need for clean water for tourism in 2028 is projected to exceed domestic water needs, namely the need for tourism water of 33.928.095 liters/day. Meanwhile, the domestic demand for clean water is only 23.545.368 liters/per day. The high demand for clean water is caused by the urbanization of the population and an increase in the number of tourists. However, the geographical conditions of Labuan Bajo in the form of an archipelago and classified as a semi-arid area can cause a decrease in the carrying capacity, requiring further research related to efforts to manage clean water.